Organizational Information Visibility and Ethical Climate among Line- Agencies in Sulu: An Assessment - Akalal, Grace A. (Future Science / FSH-PH Publications, 2025)
This is a descriptive-correlational study (Aming-Hayudini et al., 2024)that focuses on the extent of organizational information vis-ibility and ethical climate among employees of line agencies in Su-lu during Fiscal Year 2022. The results indicate that the over-whelming majority of the 200 respondent-employees were female, aged below 30 years old, with 5 or fewer years of service in the organization. Most of them were permanent employees, but nearly half are contractuals; most have completed a Bachelor's degree. In terms of organizational information visibility, the line agencies in Sulu manage information availability, approval, and accessibility at a high level. Similarly, the agencies exhibit a strong ethical climate, characterized by high ratings in egoism, benevolence, and princi-pled ethical dimensions. No significant differences in either organ-izational information visibility or ethical climate were found when data were analyzed by gender, age, length of service, appointment status, or educational attainment. Furthermore, a strong positive correlation is established between the sub-categories of organiza-tional information visibility: availability, approval, and accessibil-ity, and ethical climate: egoism, benevolence, and principled. These findings support the theoretical models by Stohl et al. (2016) on organizational information visibility and Martin & Cullen (2006) on ethical climate, which state that the proper management of or-ganizational information is very much associated with a positive ethical work climate in the line agencies of Sulu.